(untitled) (Biodiversitas Journal of Biological Diversity, 2006)
A research for biosurfactant production by mix culture bacteria which used hydrocarbon has been done. The isolates were selected for the highest biosurfactant production in SMSS (Stone Mineral Salt Solution) media suplemented with 0,1 % yeast extract b/v and 1 % v/v liquid paraffin by measuring the surface tension decrease. The selected isolate was then used for determination the best inoculum concentration and the carbon source as well for the highest biosurfactant production. Inoculum concentration variation were 5%, 10%, and 15% v/v (106 cells/mL) while the carbon source were glucose, liquid paraffin, hexadecane, and crude oil as the concentration of 1%. The decrease in surface tension was measured as parameter which corelated to biosurfactant production. The mix culture concentration of 10% was the best and decrease surface tension 6,27 dyne/cm. The inoculum concentration of 5% (v/v) and 15% (v/v) decrease surface tension 4,08 dyne/cm and 6,65 dyne/cm respectively. The best carbon source was liquid paraffin which decrease surface tension 8,34 dyne/cm while glucose, hexadecane, and crude oil were 2,81 dyne/cm; 2,46 dyne/cm; and 4,18 dyne/cm respectively. The conclusion of this research was that bacteria showed the highest biosurfactant production at the concentration of 10% and liquid paraffin as the best carbon source. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: inoculum, biosurfactan, surface tension.